The Effectiveness of the Android Application on the Lesson Bottom Pass Learning Outcomes of Volleyball for Class X Students - Septiana Dwi Cahyani; Winda Pramalia Novianti (PHEDHERAL, 2022)
Until now, after the pandemic began to subside and face-to-face learning mode is held, smartphones have become a supporting object in almost every aspect of students' daily activities, because they are considered practical and efficient. Researchers want to develop android-based interactive learning media on volleyball material that can help PJOK teachers in delivering learning materials that are interesting and easy to understand for students, so that students are not bored and learning objectives can be achieved. The android application is designed to display a variety of materials, learning videos, to cognitive assessments. The study was conducted to test the effectiveness of the Android Application towards the Learning Outcomes of Passing Down Volleyball Students in Grade X of SMAN 1 Bandongan. Based on experimental research using quantitative data analysis, it was concluded that the android application was effective and efficient on student learning outcomes, especially the basic technique of passing down volleyball.